2022
DOI: 10.1037/sgd0000459
|View full text |Cite
|
Sign up to set email alerts
|

The perks of being bi+: Positive sexual orientation–related experiences among bisexual, pansexual, and queer male youth.

Abstract: Previous research on sexual minority health has largely focused on negative experiences related to one's sexual orientation, with limited attention to the ways in which being a sexual minority can contribute to positive experiences. This is especially true of bisexual, pansexual, and queer (biϩ) male youth, whose experiences have not been represented in the literature. To address these gaps, the goal of the current study was to characterize positive experiences related to one's sexual orientation in a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
(131 reference statements)
1
7
0
Order By: Relevance
“…As noted earlier, identity affirmation is a critical dimension for LGBTQ+ people [ 60 ], and our findings appear to show this is the case across all developmental stages of life. However, as reported in previous studies [ 60 , 69 ] and explained earlier, identity affirmation is particularly crucial for people with less normative identities, such as non-binary individuals. This does not mean that identity affirmation is irrelevant for cisgender individuals, but cisgender people would likely benefit more from other types of positive identity dimensions, such as authenticity, self-awareness, freedom from social labels, personal growth, etc.…”
Section: Discussionsupporting
confidence: 52%
“…As noted earlier, identity affirmation is a critical dimension for LGBTQ+ people [ 60 ], and our findings appear to show this is the case across all developmental stages of life. However, as reported in previous studies [ 60 , 69 ] and explained earlier, identity affirmation is particularly crucial for people with less normative identities, such as non-binary individuals. This does not mean that identity affirmation is irrelevant for cisgender individuals, but cisgender people would likely benefit more from other types of positive identity dimensions, such as authenticity, self-awareness, freedom from social labels, personal growth, etc.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, overcoming shame related to one’s same-sex attractions, accepting one’s sexual orientation, and navigating how to disclose one’s sexual orientation may differ between SMM with monosexual and nonmonosexual orientations. These differences may inform the types of social support resources that SMM seek to overcome health consequences attributed to homophobic stigma (Gonzalez et al, 2017; Wang & Feinstein, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research has identified many benefits or resources derived from internalized group memberships, such as support, solidarity, and belonging (Muldoon et al, 2019). For example, many bisexual and other nonmonsexual (bisexual+) people report liking their sexual orientation because it allows them to freely love regardless of sex or gender, find community with other bisexual+ people, and engage in advocacy and activism, all of which increase the likelihood of positive identity formation and positive mental health outcomes (Flanders et al, 2017; Hagen et al, 2018; Harris et al, 2015; Wang & Feinstein, 2022). A majority of the sexual minority participants in our study identified as bisexual.…”
Section: Discussionmentioning
confidence: 99%